Efeito do condicionamento osmótico e do ácido salicílico na tolerância à dessecação em sementes de sesbania virgata (Cav.) Pers. - Voltan, Raiza Serena Barbosa (2021)
Sesbania virgata is a species with high seed production, prolonged longevity and high germination rates, in addition to being very suitable for use in reforestation programs. The objective of this work was to evaluate the effect of osmotic conditioning and salicylic acid on the desiccation tolerance of these seeds after germination. The experiment was conducted at the Forest Seeds Laboratory at the Federal University of Lavras. Initially, the seeds were subjected to 3 treatments: PEG (-0.6 MPa); PEG (-0.6 MPa) + A.S. (250 μM) and without conditioning, kept at 10ºC, for 72 h, in the dark. The germination test was carried out in a BOD-type germination chamber at 25ºC with constant white light for 72 h. After germination, the seeds were dried with or without previous incubation in PEG (-2.04 MPa), which is then taken to pre-humidification for 24 h at 20ºC and rehydration under the same germination conditions. The germination test reached 99% germination for seeds without conditioning, 98% for seeds osmoconditioned in PEG and 97% for PEG + AS. The IVG (germination speed index) was higher for PEG + AS, followed by PEG and by last, without conditioning. After direct drying, it was observed that seedlings with 1 mm of radicle length had statistically higher survival compared to 3 and 5 mm of root length in all treatments. This result was also observed in drying after incubation in PEG. Analyzing each root length after direct drying it is found that the 1 mm root length had better survival in the PEG treatment, while the 3mm root length showed better survival result for PEG and PEG + AS and finally, the 5 mm length was statistically superior in the PEG + AS treatment for seedling survival. After incubation in PEG, it was found that the 1 mm root length showed statistically superior survival in the PEG conditioning, the 3 mm root length did not show any significant difference in relation to the 3 treatments and the 5 mm length had superior results of survival in unconditioned treatment. Among the direct drying treatments, it was observed that the best was the PEG conditioning in seedlings with 1 mm of root, reaching 74% of survival. This same treatment provided the highest survival rate (90%) after incubation in PEG. It is concluded that S. virgata seedlings achieved higher survival rates at root lengths of 1 mm and seed conditioning in PEG (-0.6 MPa). Lateral root emission was also observed when the main root died in all treatments with a root length of 1 mm.